Improving village officer competence through statistics training as an effort to accelerate development in Cikanyere Village - Hagni Wijayanti; Fitria Virgantari; Siska Andriani; Bandar Anzari (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2026)
Village data and information are crucial for supporting village development. The availability of data and information will facilitate the development planning process and enable the making of appropriate and accurate decisions to advance the village based on its characteristics. However, in Cikanyere Village, problems were encountered, including incomplete data, a lack of skills and knowledge among village officials, and limited access to the latest information and technology for collecting and processing basic data. Therefore, training and assistance are needed for Cikanyere Village officials in collecting and processing simple statistical data. This activity equips 12 Cikanyere village officials with statistical skills in collecting data through Google Forms, processing data and presenting data using Excel, analyzing and interpreting results, with guidance from lecturers in utilizing technology for processing village demographic statistical data. The program was implemented through five stages: needs assessment, pretest, theoretical and practical statistics training, post-test accompanied by mentoring, and program evaluation through participant feedback. The results of the activity showed that the pretest and post-test scores increased significantly. This indicates that participants have made encouraging progress in their understanding of basic concepts related to statistical data and its role in development, as well as in data collection using Google Forms and the ability to operate Microsoft Excel to process data. The feedback results indicate that this community service activity aligns with the initiative's objectives and meets the needs of its partners. Respondents assessed that the implementing team demonstrated a professional, communicative, and responsive attitude. The community service program was not only well-received by the participants, but was also anticipated to continue in the future.